2022
DOI: 10.1007/s12274-022-4553-6
|View full text |Cite
|
Sign up to set email alerts
|

Cardiomyocyte-targeted anti-inflammatory nanotherapeutics against myocardial ischemia reperfusion (IR) injury

Abstract: Myocardial ischemia reperfusion (IR) injury is closely related to the overwhelming inflammation in the myocardium. Herein, cardiomyocyte-targeted nanotherapeutics were developed for the reactive oxygen species (ROS)-ultrasensitive co-delivery of dexamethasone (Dex) and RAGE small interfering RNA (siRAGE) to attenuate myocardial inflammation. PPTP, a ROS-degradable polycation based on PGE 2 -modified, PEGylated, ditellurium-crosslinked polyethylenimine (PEI) was developed to surface-decor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…The DSP curve exhibited strong peaks at 1713 and 1629 cm −1 , consistent with previous literature reports. 18,19 The Ce-MOFs curve displayed characteristic peaks at 1641−1554 cm −1 and 1435−1373 cm −1 , corresponding to the asymmetric and symmetric stretching vibrations of the carboxylate ion, respectively. The observed vibrations in the raw material H 2 BDC were attributed to the presence of a carboxyl group (−OCO−).…”
Section: Resultsmentioning
confidence: 99%
“…The DSP curve exhibited strong peaks at 1713 and 1629 cm −1 , consistent with previous literature reports. 18,19 The Ce-MOFs curve displayed characteristic peaks at 1641−1554 cm −1 and 1435−1373 cm −1 , corresponding to the asymmetric and symmetric stretching vibrations of the carboxylate ion, respectively. The observed vibrations in the raw material H 2 BDC were attributed to the presence of a carboxyl group (−OCO−).…”
Section: Resultsmentioning
confidence: 99%
“…The lack of an effective drug carrier that can reach and accumulate in the injured heart and then selectively release its payload to the activated CFs represents a key barrier to the pharmacological intervention of cardiac fibrosis . Most recently, although two studies have demonstrated the feasibility of redox-sensitive NPs for heart-targeted repair after MI, , it should be noted that CF-selective drug delivery capable of treating cardiac fibrosis remains unaccomplished. Here, we report the finding of Cys-based redox-responsive NPs as activated CF-targeted drug carriers.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the poor tissue penetration depth of excitation lights, the penetration depth of green or blue light is only 2 mm, which is not enough for deep tumors. Therefore, there is an urgent need to find out some new strategies to produce ROS under external stimulation with high penetrability (110). Several thirdgeneration of PSs can respond to external excitations such as NIR light, ultrasound, X-ray, chemiluminescent, bioluminescent sources, Cherenkov radiation, and implants (111).…”
Section: Light Strategies To Overcome Depth Limitationsmentioning
confidence: 99%